IN MEMORIAM: Prof. Dr. Davorin Kovačić, grad. civ. eng. (Mar. 29th, 1945 – Feb. 17th, 2019) (Rudarsko-geološko-naftni zbornik, 2019)
IN MEMORIAM:  Prof. Dr. Davorin Kovačić, grad. civ. eng. (Mar. 29th, 1945 – Feb. 17th, 2019)